The Effectiveness of Group Guidance Services Using Self Management Techniques to Reduce Smartphone Addiction - Angelina Br Sembiring; Nurussakinah Daulay (Jurnal Basicedu, 2022)
This study aims to determine whether group counseling services with self-management techniques on students have effectiveness in students with high smartphone addiction levels. This study uses counseling guidance action research or PTBK with the Pre-Test Post-Test One group design model. Participants in this study were taken from class VIII MTs Swasta Kesuma LKMD Namorambe with a population of 35 students, sampling using the Cluster Random Sampling technique as data collection, so that the sample in this study amounted to 8 students. The results of this study showed that 47% (the result of cycle II) experienced a decrease in smartphone addiction from the original 96% (pre-cycle or preliminary) at the level of student smartphone addiction.